Strategi Penanaman Nilai-Nilai Anti Korupsi pada Santri di Pondok Pesantren - Taqiuddin, Habibul Umam; Mulianahs, Baiq (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aimed to describe the understanding of students on anti-corruption values and strategies to instil anti-corruption values in students in Islamic boarding schools. This study used a qualitative approach with a descriptive research type. Data collection techniques using the interview method. Informants were selected through a purposive sampling technique. Data were analyzed using an interactive model from Miles and Huberman. The study showed that the students understood anti-corruption values, including honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage and fairness. Anti-corruption values had been applied and accustomed to through the students' daily activities while studying at Islamic boarding schools. The strategy of instilling anti-corruption values by ustadz and Islamic boarding school caretakers for the students was to introduce and get used to obeying the rules, getting used it through various activities, and providing motivation through regular recitation.